DETERMINATION OF ASSOCIATION OF PIGMENTARY GLAUCOMA WITH PIGMENT DISPERSION SYNDROME - Shah, Imtiaz Ali; Shah, Shujaat Ali; Nagdev, Partab Rai; Abbasi, Safdar Ali; Katpar, Naeem Akhtar (Journal of Ayub Medical College Abbottabad, 2017)
Background: Pigment Dispersion Syndrome (PDS) is an autosomal dominant disorder of white males between 20 to 40 years of age characterized by deposition of pigment on the lens, zonules of lens, trabecular meshwork and corneal endothelium (Krukenberg's spindle) in addition to radial, spoke like transillumination defects in the mid peripheral iris. This study was conducted to determine the frequency of occurrence of Pigmentary Glaucoma in patients with Pigment Dispersion Syndrome (PDS). Methods: This longitudinal follow up study included patients presenting with Krukenberg's spindle on the endothelial side of cornea and pigmentation of angle of anterior chamber seen on slit lamp examination and gonioscopy. Results: Seventy-two cases of PDS were included in the study, amongst them 63 (87.50%) were males. Mean age was 35.00±6.54 years (range 24-46 years). Forty-seven (65.28%) patients had an IOP in the range of 10-14 mmHg, 22 (30.56%) patients had an IOP in the range of 15-18 mmHg and 3 (4.17%) patients developed an IOP of greater than 19 mmHg. Fundoscopy showed myopic degeneration in 49 (68.06%) patients and optic disc cupping in 3 (4.17%) patients. Four (5.56%) patients had refractive error between +1D to +3D, 9 (12.50%) patients had refractive error between -1D to -4D, 21 (29.17%) patients had refractive error between -5 D to -8 D and 38 (52.78%) patients had refractive error between -9 D to -12 D. Our study showed that one patient having PDS developed glaucoma at 5 years of follow up and three patients developed glaucoma at 14 years of follow up. Conclusion: On the basis of this study we conclude that early onset primary open angle glaucoma associated with PDS or Juvenile glaucoma associated with PDS might have been mistaken as Pigmentary Glaucoma in Pakistani patients and a distinct entity in the form of Pigmentary Glaucoma may be non-existent. Keywords: Pigment dispersion syndrome; Pigmentary glaucoma; Open angle glaucoma; Pigment epithelium; Trabecular meshwork; Trans-illumination